Linearly adsorbed carbon monoxide at polycrystalline copper in aqueous phosphate buffered solution: the influence of anions, temperature and pH - J, Salimon; M, Kalaji (Malaysian Journal of Science, 2001)
The affects of pre-adsorbed anions; the temperature and pH of the electrolyte phosphate buffered solution on the formation of linearly adsorbed CO at copper surface were investigated in. The results showed that in the region where linearly adsorbed CO, Cu-COÊŸ was not observed, an adsorbed surface hydroxide, Cu(OH) band appeared at negative potentials below -0.9V. Inversely the band disappeared at potentials where CO adsorbed on the surface from -1.0 to -1.5V. The surface hydroxide qaecies was likely to form during the cathodic reduction of Cu at potentials negative to the formation of Cu(l) oxide. The results also showed that the formation of Cu-COÊŸ was dependent to solution's temperature and pH. It appeared only at low temperatures below l8Â°C. The highest peak area of Cu-COÊŸ band was obtained at pH 6.8. It was likely that the pH influenced the characteristics of the electrode surface and other competing reactions rather than influenced the CO adsorption process itself.